IMPLEMENTASI APLIKASI PENGELOLAAN DAN PELAPORAN KAS RT 01/RW 10 KECAMATAN KALIDERES BERBASIS WEB UNTUK MENINGKATKAN TRANSPARANSI DAN EFISIENSI KEUANGAN - Selvita Suci Noviyanti; Farizi Ilham; Alya Nurul Hasanah; Yulia Aprilia Sapira (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to design and implement a web-based RT/RW cash management and reporting application at RT 01/RW 10, Semanan Village, Kalideres District, West Jakarta. Currently, cash management is still carried out manually using a cash book, making the recording and reporting process less efficient and prone to errors. Cash reports to residents are delivered by posting printed sheets on bulletin boards, which limits access to financial information. This research develops an information system to assist RT administrators in managing resident data, recording cash inflows and outflows, and producing structured and transparent financial reports. The system development method is Agile, encompassing requirement planning, system design, development, testing, and user evaluation. The system is built using the CodeIgniter 4 framework, PHP programming language, MySQL database, and Apache web server. The expected outcome is a web-based RT cash management application capable of improving efficiency in financial transaction recording and enhancing transparency of financial reports for residents.